RAILWAYS AND CANALS IN THE NINETEENTH CENTURY - Himanshu Takhi (EPRA International Journal of Research and Development (IJRD), 2022)
I am going to present my paper on the much debated railways and canals system during the beginning of our colonial period. We will try and look back at the work that has been done in the following colonial period we should then claim this with detailed data. We’ll try to emulate the ways in which railways and canals had their impact on economy and see their significant contribution and see whether due to incumbency it leads to destruction of our railways and canals system which had great run before that. I’ll try and develop step by step talks about canals and railways and their positive impact on Indian economy looking the pre colonial period and try to compare it with the colonial period. We’ll study turn by turn and bring the analogies between the two. We are taking about that century when India was colonized by the British and India was going through his own transformation. Let’s talk about canals construction in India it has been widely assumed that the canal system were not so good but actually India have the best constructions of canals they have been one of the finest over the years. In terms of dimension they were pretty big and the cross sectional were huge, the throwing capacity of canals were better, the mileage it gives the average were pretty good and they were good in numbers. The canals of India were one of the greatest it has ever been come across though their structures were permanent in the nature. Now talking about railways, the rails ran first time on Indian track in 1853. Railways plays the spectacular role in the progress of country, the beginning of the railways as we have said started in 19th century. The expansion seen with the railways were huge making it to one of the largest railways in the world. The network drawn between the railways were vast in terms of connecting it. The speed with which the railways construction has happened were enormous and marvellous. The best thing that happened with railways was the expansion of trade expansion that has come simultaneously with it which India has enjoyed in the nineteenth century. The cost cutting role the railways had helped Indian entrepreneurs to earn maximum profit with the lower time interval. Railways together with canals we had brief introduction about both of them. Now we’ll talk about them in more explained way and see their role.